Hygiene and Health Coaching for Community Readiness to Perform the Hajj during an Ongoing COVID-19 Pandemic - Rr Suzy Indharty; Rustika; Budi Sylvana; Liliek Marhaendo Susilo; Tety Rachmawati; Zolaiha Zuchdi; Imron Cahyono; Mohammad Imran Saleh Hamdani; Asep Kusnali; Dede Anwar Musadad; Muhammad Firdaus; Al Asyary; et al. (Tropical Medicine and Infectious Disease, 2023)
In March 2020, WHO declared Coronavirus Disease 2019 (COVID-19) as a global pandemic, which had a major impact on all mass gatherings (MG), including the Hajj. This has an impact for the government, as the party organizing the pilgrimage can make more mature preparations for a more optimal implementation of the pilgrimage. This study aimed to evaluate hygiene and health coaching for community readiness to perform the Hajj during an ongoing COVID-19 pandemic in Indonesia. We used a mixed qualitative and quantitative method, in which the quantitative component used an analytic cross-sectional design with a questionnaire given to 2425 pilgrims, while the qualitative component was carried out through Focus Group Discussion. During the pandemic, all hygiene and health coaching, including guidance, was carried out in three types of distance learning, called “online”, “offline (face-to-face)”, and “combination”. This study shows that face-to-face health coaching is low (50.5%), while online coaching is high (70.0%). The total fraction of pilgrims who participated in blended coaching sessions was 55.1%, and the highest frequency of coaching was under four times (38.7%). However, in its implementation, there is still no integration between programs. There is quite a lot of health information given to pilgrims, but the material still varies between regions. Information on guidelines for preventing and transmitting COVID-19 for officers and pilgrims has not been fully socialized. There exists an urgent need to establish messages that are clear, meaningful, empathetic, consistent, and in context in order to achieve health improvement of pilgrims.